Antagonistic Activity of Bacteriocin-producing Lactobacillus Against Candida spp - Mohsin, Zainab Abdulridha; Ali, Wala’a Shawkat (Iraqi Journal of Science, 2021)
In order to screen antifungal activity of lactobacilli that produce bacteriocin against the yeast Candida, ninety-two food and clinical samples were collected. Also, several commercial brands of Lactobacillus probiotics and ready-made isolates of Lactobacillus were used. The isolated lactobacilli were subjected to microscopic, macroscopic, and biochemical tests. Moreover, molecular identification was performed for the best producer isolate. For Candida spp. isolation, seventy- two samples were collected from different clinical sources; in addition, nine of ready-made isolates were also used. All the isolated Candida spp. were subjected to microscopic and macroscopic examinations which were confirmed by VITEK® 2 YST card automated system. Detection of bacteriocin production from Lactobacillus was investigated by primary and secondary screening techniques and the results showed that the agar wells diffusion method was the best. The most efficient isolate to produce bacteriocin was L. plantarum WZD3, in which antifungal activity of bacteriocin was at the level of 80 and 40 AU/ml against the most sensitive Candida isolates; C. albicans CA and C. albicans CB, respectively. After partial purification of bacteriocin by n-butanol extraction method, bacteriocin activity was increased to 320 AU/ml against both yeast isolates. In conclusion, L. plantarum WZD3 or its bacteriocin could be a good candidate as antifungal agent to treat Candida infections and more studies are required to evaluate its acivity against other types of medical fungi.